Thermal history modeling of the L chondrite parent body - Gail, Hans-Peter; Trieloff, Mario (Arxiv, 2019)
The radius of the L chondrite parent body, its formation time, and its evolution history are determined by fitting theoretical models to empirical data of radioisotopic chronometers for L chondrites. A simplified evolution model for the L chondrite parent body is constructed considering sintering of the initially porous material, temperature dependent heat conductivity, and an insulating regolith layer. Such models are fitted to thermochronological data of five meteorites for which precise data for the Hf-W and U-Pb-Pb thermochronometers have been published. A set of parameters for the L chondrite parent body is found that yields excellent agreement (within error bounds) between a thermal evolution model and thermochonological data. Empirical cooling rate data also agree with the model results within error bounds such that there is no conflict between cooling rate data and the onion-shell model. Two models are found to be compatible with the presently available empirical data: One model with a radius of 115 km and a formation time of 1.89 Ma after CAI formation, another model with 160 km radius and formation time of 1.835 Ma. The central temperature of the smaller body remains well below the Ni,Fe-FeS eutectic melting temperature and is consistent with the apparent non-existence of primitive achondrites related to the L chondrites. For the bigger model incipient melting in the central core region is predicted which opens the possibility that primitive achondrites related to L chondrites could be found.
Gesehen am 30.06.2021